Comparision of Distal Uniplanar Locking with Biplanar Distal Locking in Intramedullary Interlocking Nailing of Fractures Distal Shaft of Tibia - Ahmad, Rana Shahbaz; Amin, Muhammad Suhail; Rathore, Muhammad Omar; Hassan, Bushra; Iqbal, Javaid; Qamar, Adeel (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the effects of distal uniplanar locking and distal bi planar locking on union times in uncomplicated fractures distal shaft of tibia managed with an intramedullary interlocking nail.Study Design: Comparative prospective study.Place and Duration of Study: Department of Orthopedics and Trauma Combined Military Hospital Rawalpindi from Jan to Nov 2020.Methodology: Fifty-three patients having fractures distal shaft of tibia managed with intramedullary interlocking nail were studied. Twenty-nine patients were managed using two interlocking screws distally (uniplanar) in coronal plane (group-1). Twenty-four patients were managed with three bi planar screws comprising two coronal and one sagittal distal interlocking screw (group-2). Patients were followed every 4 weeks, and bone union time was assessed. Isolated closed fractures treated with closed reduction were included.Results: Patients treated with distal bi planar locking (group-2) had significantly reduced union time in weeks (11.25 ± 1.42) compared to uniplanar distal interlocking (group-1) (15.79 ± 1.80) (p